Body fat distribution in Parkinson's disease: An MRI-based body fat quantification study. (December 2016) - Bernhardt, Denise; Müller, Hans-Peter; Ludolph, Albert C.; Dupuis, Luc; Kassubek, Jan
Abstract: Introduction: There is some evidence that Parkinson's Disease (PD) patients have lower body weight and lower fat mass when compared to healthy subjects and that lower body weight and fat mass influence disease risk and progression. It remains unclear, however, if weight loss of fat mass loss occurs only in a subgroup of patients and whether fat distribution is altered during PD. The aim of this study was to prospectively investigate adipose tissue content and distribution in PD patients. Methods: The body fat composition of PD patients (N = 54) was compared with age matched healthy controls (N = 55) using a magnetic resonance imaging (MRI)-based method. A longitudinal MRI scan was acquired in 25 PD patients after a mean follow up period of 12 months. Results: The volume of total body fat as well as of visceral fat showed no difference between PD patients and healthy controls at baseline or at follow up. However, PD patients displayed decreased subcutaneous fat tissue (p = 0.01) and a higher visceral to subcutaneous fat ratio as compared to controls (p = 0.004). After follow up, 16 PD patients did not lose weight, while 9 PD patients lost between 0.5 and 10 kg. Conclusion: Fat distribution is altered in PD patients, with an increased ratio of visceral to subcutaneous fat. Highlights: Body composition investigated by MRI showed no alteration in total body fat in PD. PD patients showed a higher visceral to subcutaneous fat ratio compared to controls. Weight loss in PD was associated with increased visceral to subcutaneous fat ratio. Fat distribution in PD patients was worsened by weight loss during disease progression.